Microwave‐Assisted Catalytic Amination of Phenothiazine; Reliable Access to Phenothiazine Analogues of Tröger's Base. Issue 24 (16th July 2013) - Găină, Luiza I.; Mătărângă‐Popa, Larisa N.; Gal, Emese; Boar, Paul; Lönnecke, Peter; Hey‐Hawkins, Evamarie; Bischin, Cristina; Silaghi‐Dumitrescu, Radu; Lupan, Iulia; Cristea, Castelia; Silaghi‐Dumitrescu, Luminiţa
Abstract: Efficient protocols for microwave‐assisted catalyzed amination of halogeno‐phenothiazines are described. Phenothiazine analogues of Tröger's base (PTB) were obtained by condensation of amino‐phenothiazines with formaldehyde in HCl/EtOH/H2 O and structurally characterized by NMR and XRD analyses. The formation of PTB isomers was predicted by computational analysis based on theoretical methods (DFT and HF). Electronic properties of the parent amino‐phenothiazines and PTB were assessed on the basis of cyclic voltammetry and UV/Vis absorption/emission spectroscopy data. The compounds exhibit blue fluorescence emission characterized by extremely large Stokes shifts (8900–10300 cm –1 ) in both dilute solutions and aggregated states. Interactions with different types of biomolecules show the capacity of binding to proteins and DNA, with effects on prooxidant reactivity including lipid peroxidation. Abstract : Microwave‐assisted catalyzed amination of halogeno‐phenothiazines provides precursors for phenothiazine analogues of Tröger's base. DFT and HF computational analysis, electronic properties (fluorescence emission in solution and solid state), and binding to proteins and DNA with effects on prooxidant reactivity were investigated.